Cooking contests for healthier recipes: Impacts on nutrition knowledge and behaviors in Bangladesh - Kramer, Berber (International Food Policy Research Institute, 2017)
Many poverty alleviation programs aiming to enhance nutrition include behavior change communication (BCC). This study uses a field experiment in Bangladesh to assess the impacts of BCC, focusing on nutrition training (providing information) and cooking contests (providing experience). First, in 900 households, we tested the nutrition knowledge of two household members and invited one of them to participate in a nutrition training. Comparing differences in pre-training and post-training knowledge among trained and nontrained household members, we find that training has a positive effect on nutrition knowledge, but the improved knowledge does not translate into healthier diets. Second, in randomly selected neighborhoods, the nutrition training was followed by a cooking contest designed to reinforce nutrition training messages and encourage participants to learn by doing. We find no additional effects of these contests on either knowledge or diets. We conclude that low-cost BCC strategies help improve knowledge, but alternative interventions are needed to strengthen links between knowledge and behavior.